A Sandwich-Type Electrochemical Immunosensor Using Antibody-Conjugated Pt-Doped CdTe QDs as Enzyme-Free Labels for Sensitive HER2 Detection Based on a Magnetic Framework - Ehzari, Hosna; Safari, Meysam (Frontiers in Chemistry, 2022)
Tumor markers are highly sensitive and play an important role in the early diagnosis of cancer. We developed an electrochemical sandwich-type immunosensor that detects human epidermal growth factor receptor 2 (HER2). Magnetic framework (Fe3O4@ TMU-24) and AuNPs (Fe3O4@ TMU-24 -AuNPs) are utilized in this sensing platform. In addition to their high specific surface area and excellent biocompatibility, Fe3O4@ TMU-24-AuNPs nanocomposites exhibited excellent electrocatalytic properties. The primary antibody of HER2 (Ab1) was immobilized on the surface of the Fe3O4@ TMU-24-AuNPs. In this sensing method, palatine doped to CdTe QDs (Pt: CdTe QDs) is utilized as a novel labeling signal biomolecule (secondary antibodies). Pt: CdTe QDs own good biocompatibility and excellent catalytic performance. The amperometric technique was used to achieve the quantitative determination of HER2 by using a sandwich-type electrochemical immunosensor. Under the optimum conditions, the dependency of the current signal and HER2 concentration showed a linear region from 1 pg ml−1–100 ng ml−1 with 0.175 pg ml−1 as the limit of detection. This biosensing device also showed long stability and good reproducibility, which can be used for the quantitative assay of HER2.